Rancang Bangun Mesin Pembuat Abon Ubur-ubur - ., Junaidi1; Kurnianto, Rudi; Uslianti, Silvia; Wahyudi, Tri (Faculty of Engineering, Universitas Tanjungpura, 2014)
Abstract– Paloh Temajuk Village District of Sambas district is one of the villages bordering with Sarawak (East Malaysia). One potential seafood commodity of Temajuk Village is a jellyfish. Problems faced by fishermen today is prices of dried jellyfish continue to fall. Based on the problems above, it is necessary to process jellyfish to increase the sale value. Terms of quality and food safety testing shall be in accordance with the type of chemical test (SNI 7690.1-201 Shredded Fish products). The conclusion is that shredded jellyfish product does not meet the requirements of chemical tests (ISO specifications Shredded Fish). Keywords– Shredded jellyfish, shredded Machine, spinner Machine